Implementation of Law No. 23 of 2011 Concerning Zakat Management in Poverty Alleviation (Baznas Pangkep Regency) - Nur Fajri Septiana; Syahruddin Nawi; Dachran S. Busthami (Manunggal Halim Jaya, 2025)
The purpose of this study is 1) to examine and analyze the implementation of Law No. 23 of 2011 on Zakat Management in alleviating poverty (Baznas Pangkep Regency), and 2) to identify and analyze the factors affecting the implementation of Law No. 23 of 2011 on Zakat Management. This research employs an empirical legal research method, conducted at the Baznas Pangkep Regency office. Data were collected through interviews and questionnaires, and analyzed descriptively. The findings of the study show that the implementation of Law No. 23 of 2011 on zakat management in alleviating poverty at Baznas Pangkep Regency has not been optimal. This is due to several challenges in zakat management, such as limited public outreach about the importance of zakat, and the insufficiently effective economic empowerment programs aimed at improving the long-term welfare of mustahik. The factors influencing the implementation of Law No. 23 of 2011 include legal structure, legal substance, and legal culture. Based on the findings, the study recommends: 1) Baznas Pangkep Regency should enhance the socialization of Law No. 23 of 2011 on zakat management comprehensively to the public, develop professional human resources, and ensure zakat management runs effectively, transparently, and accountably in accordance with Islamic principles; 2) Baznas Pangkep Regency should strengthen mustahik economic empowerment programs and improve zakat distribution to ensure it reaches the targeted groups for sustainable poverty alleviation.